Determinan keputusan penggunaan layanan mobile banking bank syariah - Putri Kamila, Talia; Aslamatis Solekah, Nihayatu (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2025)
This study aims to analyze the influence of ease of use, service quality, and lifestyle on the decision to use Islamic bank mobile banking services among gen z. This research is quantitative, using an explanatory research method. The subjects of this study are gen z individuals located in Malang city, with a total of 232 respondents. The sampling technique used in this study is purposive sampling. Data collection was carried out through the distribution of questionnaires. The data analysis technique used is multiple linear regression analysis with the assistance of IBM SPSS Statistic version 25.0 software. The results of the study indicate that ease of use, service quality, and lifestyle influence the decision to use islamic bank mobile banking services, both partially and simultaneously. The findings of this study show that the lifestyle variable has a greater value compared to ease of use and service quality, meaning that the lifestyle of gen z in Malang city predominantly influences the decision to use islamic bank mobile banking services. The limitation of this study is that the sample is limited to gen z only in Malang city.